Intelligence Quotient Variability in Klinefelter Syndrome Is Associated With GTPBP6 Expression Under Regulation of X-Chromosome Inactivation Pattern - Simonetti, Luciane; Ferreira, Lucas G. A.; Vidi, Angela Cristina; Souza, Janaina Sena de; Kunii, Ilda S.; Melaragno, Maria Isabel; Mello, Claudia Berlim de; Carvalheira, Gianna; Dias da Silva, Magnus R. (Frontiers in Genetics, 2021)
Klinefelter syndrome (KS) displays a broad dysmorphological, endocrinological, and neuropsychological clinical spectrum. We hypothesized that the neurocognitive dysfunction present in KS relies on an imbalance in X-chromosome gene expression. Thus, the X-chromosome inactivation (XCI) pattern and neurocognitive X-linked gene expression were tested and correlated with intelligence quotient (IQ) scores. We evaluated 11 KS patients by (a) IQ assessment, (b) analyzing the XCI patterns using both HUMARA and ZDHHC15 gene assays, and (c) blood RT-qPCR to investigate seven X-linked genes related to neurocognitive development (GTPBP6, EIF2S3, ITM2A, HUWE1, KDM5C, GDI1, and VAMP7) and XIST in comparison with 14 (male and female) controls. Considering IQ 80 as the standard minimum reference, we verified that the variability in IQ scores in KS patients seemed to be associated with the XCI pattern. Seven individuals in the KS group presented a random X-inactivation (RXI) and lower average IQ than the four individuals who presented a skewed X-inactivation (SXI) pattern. The evaluation of gene expression showed higher GTPBP6 expression in KS patients with RXI than in controls (p = 0.0059). Interestingly, the expression of GTPBP6 in KS patients with SXI did not differ from that observed in controls. Therefore, our data suggest for the first time that GTPBP6 expression is negatively associated with full-scale IQ under the regulation of the type of XCI pattern. The SXI pattern may regulate GTPBP6 expression, thereby dampening the impairment in cognitive performance and playing a role in intelligence variability in individuals with KS, which warrants further mechanistic investigations.